Effect of Dike Width on Pore Pressure and Water Content Evolution During Overtopping Conditions - Hassan, Marwan A.; Shaalan, Heyam H.; Al-Deewan, Hayder A. O. (Civil Engineering Journal, 2026)
The failure of dike embankments due to overtopping flow plays a crucial role in understanding the mechanisms behind dike erosion, which is essential for effective disaster mitigation. The "SLIDE" program was used to analyze the transient response of pore water pressure (PWP) and volumetric water content (VWC) within a homogeneous coarse sand bed. The authors have previously examined the use of seepage-control elements in 3D simulations of embankment breach failures due to overtopping, conducted in laboratory flumes at the University of Science of Malaysia. In this study, pore water pressure (PWP) and volumetric water content (VWC) were measured at various points beneath the crest and along both the upstream and downstream slopes for three different dike crest widths: 7 cm, 12 cm, and 18 cm. This paper also presents a factor of safety (FOS) analysis across the unsaturated–saturated zones within the dike embankment during the events of overtopping moments until full saturation of the downstream slope. The results indicate that increases in both PWP and VWC occurred across all test groups along the slopes. Narrower crest widths led to higher pore water pressure at the onset of overtopping, while wider crest widths resulted in increased pore pressure toward the end of the erosion process. A reduction in the factor of safety was observed along the crest and downstream slope. However, in dikes with wider crest widths, the length of the embankment decreased due to prolonged flow discharge through the downstream toe and remnants of the upstream slope. The transient flow and slope stability results provide new insights into the coupled hydromechanical behavior of dike soil during overtopping events.